Pompoms ; Pik Pak Pow ; Matters of movement [videorecording] - Lazaro, Cheche (The Probe Team, 1989)
A second look at the pedophile situation in Pagsanjan. Focuses on action films. Two dancers, Elizabeth Roxas and Stephen Smith talk about their craft as artist in modern form.